Peningkatan Kesadaran Pengelolaan Sampah Pesisir melalui Aksi Bersih Pantai di Pantai Labuan Petung, Desa Sekotong Barat, Kabupaten Lombok Barat - Muhammad Marzuki; Bagus Dwi Hari Setyono; Dwi Aprilianingsih; Weni Rahmawati; Winggi Anggita; Sima Lafina Ziqri; Gina Maulina; Sahrul Alim; Awan Dermawan; Rizky Regina Kawirian (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service article describes the implementation of a beach clean-up program and examines its contribution to strengthening awareness of coastal waste management at Labuan Petung Beach, Sekotong Barat Village, West Lombok Regency. The activity was conducted on 21 September 2025 using a participatory approach consisting of a preliminary site survey, identification of priority cleaning areas, implementation of the clean-up action, observation of dominant waste types, and a brief collective reflection with participants. The results showed that the collected waste was dominated by single-use plastics, particularly plastic bags, beverage bottles, and styrofoam that had accumulated in the intertidal zone. The active involvement of students, community leaders, and local residents indicates that the activity functioned not only as an environmental clean-up intervention but also as an educational medium for strengthening community concern for coastal waste management. Therefore, beach clean-up activities can be positioned as an important entry point for fostering participation and supporting more sustainable coastal environmental management.